Advances in Human Factors, Business Management and Society Proceedings of the AHFE 2018 International Conference on Human Factors, Business Management and Society, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Kantola, Jussi Ilari; Nazir, Salman; Barath, Tibor; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents practical approaches for facilitating the achievement of excellence in the management and leadership of organizational resources. It shows how the principles of creating shared value can be applied to ensure faster learning, training, business development, and social renewal. In particular, it presents novel methods and tools for tackling the complexity of management and learning in both business organizations and society. Discussing ontologies, intelligent management systems, methods for creating knowledge and value added, it offers novel insights into time management and operations optimization, as well as advanced methods for evaluating customers' satisfaction and conscious experience. Based on two conferences, the AHFE 2018 International Conference on Human Factors, Business Management and Society, and the AHFE 2018 International Conference on Human Factors in Management and Leadership, held on July 21-25, 2018, in Orlando, Florida, USA, the book provides bothresearchers and professionals with new tools and inspiring ideas for achieving excellence in various business activities.
Keywords: Industrial Management; Strategic planning; Leadership; Data mining; Personnel management; Operations research; Computational intelligence; Industrial Management; Business Strategy and Leadership; Data Mining and Knowledge Discovery; Human Resource Management; Operations Research and Decision Theory; Computational Intelligence